1995
DOI: 10.1210/endo.136.11.7588265
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated effects of insulin-like growth factor I on inhibitory pathways of cell cycle progression in cultured cardiac muscle cells.

Abstract: Insulin-like growth factor I (IGF I) plays a key role in the regulation of cell proliferation. Progression of the cell cycle is regulated by stimulatory and inhibitory pathways. In order to understand the mechanisms through which IGF I regulates cardiac muscle growth, we have studied the effects of IGF I on inhibitory pathways involving p53 and WAF1 in cultured cardiac muscle cell line H9C2. The onset of DNA synthesis in response to IGF I stimulation was preceded by activation of p53 expression. In addition, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…This finding is in keeping with the recent observation of an IGF-I stimulating effect on p53 expression in cardiac muscle cells [31]. This finding is in keeping with the recent observation of an IGF-I stimulating effect on p53 expression in cardiac muscle cells [31].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in keeping with the recent observation of an IGF-I stimulating effect on p53 expression in cardiac muscle cells [31]. This finding is in keeping with the recent observation of an IGF-I stimulating effect on p53 expression in cardiac muscle cells [31].…”
Section: Discussionsupporting
confidence: 91%
“…Under the culturing conditions used in the present paper, with exponentially dividing cells, we could not detect any myoblast fusion, which would indicate differentiation towards a more skeletal muscle cell-like phenotype. Another rationale for using H9c2 cells is that they express specific surface receptors for IGF-I, which has been shown to stimulate H9c2 cell proliferation (Chen et al 1995, Bahr et al 1997 and inhibit apoptosis (Wang et al 1998). This would be an advantage when choosing H9c2 as a cardiomyocyte cell line to investigate stimulatory effects of endocrine factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in several studies to investigate different cellular mechanisms in cardiomyocytes (Sipido & Marban 1991, Wu et al 1996, Chen et al 2000 and has been shown to be responsive to IGF-I (Chen et al 1995, Bahr et al 1997.…”
Section: Introductionmentioning
confidence: 99%
“…For example, H9c2 cells respond to arginine vasopressin with a rapid and substantive release of S(E)R Ca 2+ stores, followed by gradual repletion of these stores over hours‐days concurrent with the development of hypertrophy [Reilly et al, 1998; Brostrom et al, 2000, 2001]. H9c2 myocytes possess receptors for insulin‐like growth factor‐I [Chen et al, 1995; Hong et al, 2001] but not for basic fibroblast growth factor‐2 [Sheikh et al, 1997]. We report here that H9c2 cells express classical PDGF‐β receptors, PDGF‐BB serves as a full mitogen for these cells, and persistent depletion of S(E)R Ca 2+ stores delays the mitogenic response.…”
mentioning
confidence: 99%